МЕЖДУНАРОДНО-ПРАВОВОЙ ОБЗОР ДИРЕКТИВ ЕВРОПЕЙСКОГО СОЮЗА ПО ВЫБРОСАМ ИЗ ПРОМЫШЛЕННЫХ ОБЪЕКТОВ (Journal of actual problems of jurisprudence, 2019)
This article addresses the issue of European Directives on issues of industrial facilities.